1984
DOI: 10.1182/blood.v64.3.701.701
|View full text |Cite
|
Sign up to set email alerts
|

Lineage switch in acute leukemia

Abstract: Conversions of leukemic cell lineage (lymphoid or myeloid) have been reported only rarely. Our review of the cytochemical and immunophenotypic features of 89 cases of childhood leukemia in marrow relapse indicated lineage switch (lymphoid to myeloid or the reverse) in six patients (6.7%). Five patients with acute lymphoblastic leukemia (ALL) at diagnosis had converted to acute nonlymphoblastic leukemia (ANLL), and one had converted from ANLL to ALL. Each child received lineage-specific multiagent chemotherapy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
0

Year Published

1985
1985
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 204 publications
(45 citation statements)
references
References 23 publications
1
44
0
Order By: Relevance
“…Detection of atypical antigen expression by double color immunofluorescence implies that the antigenic features identified at diagnosis remain the same during the course of the disease. Differences in the immunophenotype as well as lineage switching in relapsing leukemias have been described previously (6,7,23,26). Of note, the leukemia-associated antigen combinations were retained at relapse in 11 of 12 cases; the only patient with a change in phenotype and FAB-based criteria as well represented a case of AML after MDS.…”
Section: Discussionsupporting
confidence: 54%
“…Detection of atypical antigen expression by double color immunofluorescence implies that the antigenic features identified at diagnosis remain the same during the course of the disease. Differences in the immunophenotype as well as lineage switching in relapsing leukemias have been described previously (6,7,23,26). Of note, the leukemia-associated antigen combinations were retained at relapse in 11 of 12 cases; the only patient with a change in phenotype and FAB-based criteria as well represented a case of AML after MDS.…”
Section: Discussionsupporting
confidence: 54%
“…The existence of a pluripotent stem-cell capable of differentiation along the myeloid and lymphoid pathways has been suggested based on evidence from cases of biphenotypic leukemia in which a simultaneous or rapid switch from one to another lineage has occurred (Perentesis et al, 1983;Lanham et al, 1984;Stass et al, 1984). The high expression of 3C5 in 3 out of the 4 TdT+ AML cases (Table 2) in which a proportion of cells displayed simultaneously lymphoid (TdT+) and myeloid (SBB and MPO) markers together with the positivity in M1 AML and common ALL suggests that 3C5 is expressed in an early progenitor cell (presumably TdT+) capable of undergoing either B-lymphoid (TdT + , 3C5 + , J5 +) or limited myeloid differentiation TdT + / -,3C5 + , MPO+).…”
Section: Discussionmentioning
confidence: 99%
“…Treatment recommendations for lineage switch leukaemia are scarcely found in the literature. Stass et al (1984) reported an achievement of remission with treatment adjusted to the phenotype evident at lineage switch after initial lineage-specific chemotherapy. Only three of our eight lineage switch patients, all carrying a trisomy 8, are still alive ( Figure S1B).…”
Section: Treatment and Outcomementioning
confidence: 99%